Kapasitas Manajemen Program dan Proses Pemerintah Desa Jangkurang dalam Memberikan Pelayanan BLT Dana Desa - Nuradha Azzahra, Shinta; Sukarno, Dedi (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2024)
To support accelerating extreme poverty elimination, the Government of Indonesia established the Village Fund Cash Assistance (BLT-DD) program to provide direct cash assistance to residents in rural or remote areas, including Jangkurang Village. In providing BLT-DD services, good organizational capacity is required from the Jangkurang Village Government, especially in program management and process management. However, in practice, this has not been adequate. This research further explains the program and process management capacity of the Jangkurang Village Government. The method used is qualitative through data collection techniques, namely interviews, observations, and documentation studies. Based on the research, the capacity of program and process management at the Jangkurang Village Government still needs improvement in several aspects. Factors that can be identified are the lack of document ownership, delays in registering KPM candidates, inadequate infrastructure conditions, misalignment in the process regarding reporting, and limited access to information. Therefore, improvements to the capacity of program management and process management need to be made.